Determination of volatile oil compounds and antioxidant activities of some Cirsium taxa grown in Türkiye - ÖZLEM SARAL; MUSTAFA KARAKÖSE (Nusantara Bioscience, 2024)
Abstract. Saral Ö, Karaköse M. 2024. Determination of volatile oil compounds and antioxidant activities of some Cirsium taxa grown in Türkiye. Nusantara Bioscience 16: 62-67. Several Cirsium taxa are commonly used as a folk remedy or food in Anatolia and some countries. The study aims to determine the volatile oil profile and antioxidant activity of endemic Cirsium trachylepis Boiss., Cirsium echinus Hand.-Mazz., and Cirsium osseticum Petr. subsp. osseticum. The volatile oil compounds of three Cirsium species were analyzed by Gas Chromatography-Mass Spectrometry (GC-MS) using Solid Phase Microextraction (SPME). Additionally, total phenolic content was measured, and antioxidant activity capacity was determined by FRAP and DPPH• analyses in three Cirsium taxa methanolic extracts. A total of 32 (87.89%), 25 (88.69%), and 27 (80.68%) volatile compounds were identified from C. trachylepis, C. osseticum subsp. osseticum, and C. echinus, respectively. Pentadecanolide was the major volatile oil in three Cirsium species and was first reported in Cirsium taxa in this study. When the fatty acid content was examined, palmitic acid was determined as the common and main fatty acid for the three Cirsium species. A comparison of the antioxidant activity of three species showed that C. echinus had the highest antioxidant activity. The total phenolic content of C. echinus was found to be 250.84±0.46 mg GAE/100 g sample. While the FRAP value of C. echinus was 36.47±1.04 µmol Fe/g sample, the SC50 value was 1.89±0.05 mg/mL. This study may pave the way for the determination of volatile oils by SPME and the further development of research on Cirsium taxa.